PELATIHAN PENGGUNAAN MODUL RMA SOFTWARE ACCURATE BAGI SISWA SMA KRISTOFORUS I - Sriwati; Novia, Jessica; Sutedja, Natasya Emillia (Jurnal Serina Abdimas, 2024)
After-sales service is one of the important things that customers pay attention to when purchasing an item. Therefore, every company must have adequate after-sales service procedures. With the role of information technology, the customer claims process can also utilize accounting software. In a company, after-sales service can have an impact on company resources, but this activity is rarely discussed in accounting lessons, especially at the high school level. For this reason, the PKM Team took the initiative to conduct training regarding the use of software for after-sales service at SMA Kristoforus 1. One of the accounting software that provides a feature for recording customer claims is Accurate. In this software there is a Return Merchandise Authorization (RMA) module which can be used to record customer claims. The participants in this training are SMA Kristoforus 1 students who take accounting extracurriculars. The PKM team will provide a material presentation which will then be followed by practice on how to use the RMA module, which includes recording customer claims, results of the customer claim process, billing, and receiving payments. This training was carried out in November 2023 in the computer room of SMA Kristoforus 1. At the end of the training session, the PKM Team also provided practice questions for the participants to do independently and all participants were able to do them correctly, so it could be concluded that they were able to operate RMA module.